Tiger: The Real Story - Helling, Steve (Perseus Books Group, 2010)
Born to a father who described him as the (3z(Bchosen one(3y (Band a mother who called him the (3z(Buniversal child,(3y (BTiger Woods was groomed for the fame and influence that his parents believed was his destiny. At age twenty, he made his debut in a Nike commercial. (3z(BHello, world,(3y (Bhe said. (3z(BAre you ready for me?(3y (BThe world was ready. For the next thirteen years, Tiger nearly lived up to his parents$1 (Boutsized expectations. He conquered the world of golf, settled down with a beautiful Swedish model, and started a family. His net worth approached one billion dollars. Everything was going according to plan$1 (Buntil the scandal hit.s
Keywords: Non-Fiction / Biography - Tiger Wood